Estimating Heating and Cooling Loads Software - Ahmad Ismail (My University, 2020)
The heating and cooling loads estimation plays a vital role in hardware sizing estimation and cost estimation to purchase , or to run and to estimate marginal profits when it comes to business goals. Because now a day’s a lot of power consumed to run heating ventilation air conditioning (HVAC) systems. To improve system efficiency, the calculation of lads should be made quickly and accurate, so we created this software to calculate heating loads rapidly and accurate. The main object from this software is to do calculations of heating loads by entering the required information such as locations(country , city),building materials , working time , season or month , wall construction, orientation ,and the geometry of building, then the software provide the desired calculation and results . This software will cover the capital cities of the entire world but it will focus on the middle east, especially, West bank and Gaza, Jordan, Saudi Arabia, emirates and Qatar using its code. This software based onto visual basic language. Step by step the data input will be given as per the architectures design and finally the result sheet will come after finishing all data input. So, this software will decrease efforts, time consumed, improve the accuracy and will be easily to deal with.